Digitalisasi Arsip Dokumen Pegawai RSUD Prof. Dr. Soekandar Kabupaten Mojokerto - Yusmanisari, Eka; Tiyodanto, Indhy Jazilla; Umriha, Shilfatul; Mulyo, Ganang Putro; Aditya, Muhammad Febrian (Jurnal Abdimas Jatibara, 2023)
Handling the management of Prof. dr. Soekandar Hospital Personnel Documents. with the high volume of employee documents managed. From this, several obstacles were encountered in the process of searching for employee documents, pension projections, projected salary increases and employee recapitulation. For that, we need an information system that can handle these problems. The activities carried out aim to provide an overview of procedures for digitizing archives by considering various aspects of decency, so as to guarantee storage efficiency and ease of access to archives (accessibility).